Pemodelan struktur bawah permukaan berdasarkan data anomali magnetik tereduksi ke kutub di kawasan prospek bijih emas desa paningkaban kecamatan Gumelar kabupaten Banyumas - Syimah Nur Rahmah Shabrina; Muhammad Sehah; Sukmaji Anom Raharjo (Jurnal Teras Fisika: Teori, Modeling, dan Aplikasi Fisika, 2023)
The research was carried out in the gold ore prospect area of ​​Paningkaban Village, Gumelar District, Banyumas Regency. This research aims to map magnetic anomaly data and model subsurface geological structures in two dimensions (2D) based on tilt derivative analysis of magnetic anomalies data which are reduced to the poles. The tilt derivative filter serves to reinforce the boundaries of geological structures, especially faults and intrusive rocks, thus facilitating the interpreting process of magnetic anomalies data. Magnetic field data processing is carried out to obtain local magnetic anomalies data. Furthermore, the local anomalies data are reduced to the poles, in order to obtain local magnetic anomalies data reduced to the poles with values ranging from -381.8 nT – 218.7 nT. Based on the tilt derivative analysis, the high-value anomaly contrast patterns are in the east - west direction. This can be interpreted as a pattern of distribution of fault structures and intrusive rock bodies in the research area which is a path of gold mineralization. 2D-modeling has been carried out using Geosoft Oasis Montaj v. 8.4 to obtain the subsurface geological structure model in the AA', BB', and CC' sections. The 2D-modeling results show that in the AA' section there is one andesitic intrusion, in the BB' section there are two andesite intrusions, and in the CC' section there are one intrusion and one fault. The intrusive rock is thought to be the location of gold mineralization.